(untitled) (Medical Forum Monthly, 2021)
Objective: To see if orthoptic exercise improves convergence insufficiency (CI). Study Design: A Cross-Sectional Study Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Al-Ibrahim Eye Hospital, Karachi for 08 months Jan.2020 to Aug. 2020. Materials and Methods: 60 numbers of patients suffering from CI were taken in the study after taking consent from them. The near point of convergence (NPC) and the fusional range of all the patients were measured. All patients were prescribed pencil push-up tests for one month after which all variables were reassessed. To assess the difference that orthoptic exercise had on CI patients, one-way ANOVA chi-square test was applied keeping the P-value≤0.05 as statistically significant. Results: Significant difference (P-value≤0.05) in all measured variables after patients carried out pencil push-up tests for one month. NPC improved in all patients along with improvement in fusional amplitude. Conclusion: It can be concluded that Orthoptic exercises had a beneficial effect on patients with CI. It is still the primary treatment option when it comes to reducing the symptoms of CI.